Effect of buffalo urine application on sheath blight disease caused by Rhizoctonia solani of rice (Oryza sativa)* - RAJA, J (The Indian Journal of Agricultural Sciences, 2011)
The effect of quantity and time of buffalo urine application to control sheath blight disease of rice was studied during 2005â€“06. The disease was very effectively controlled with buffalo urine applied once at the panicle-differentiation stage at 100 l/ha, followed by booting stage and to a lesser extent at the heading growth stage. This treatment also resulted in a significantly higher yield compared with the inoculated check. Sheath blight disease developed during the internode formation to boot split growth stage and caused yield losses. Hence, when the urine application was delayed beyond panicle differentiation or boot stage it could not control sheath blight disease. Â